Analisis Faktor yang Mempengaruhi Kejadian Penyakit ISPA di Kelurahan Nelayan Indah - A, Yulia Khairina; k, Anzani Ashary; Zuhrah, Alya (Program Studi PGMI Sekolah Tinggi Ilmu Tarbiyah Nahdlatul Ulama Al Hikmah Mojokerto, 2023)
Humans and the environment are an inseparable unit, interact with each other, and in a good environment harmonious and balanced interactions are established. The research location is in the Village of Nelayan Indah, Medan Labuhan District. The type of research used is descriptive quantitative with a cross sectional research design, which aims to determine what factors influence the incidence of ARI disease in Nelayan Indah Village. The sample in this study amounted to 210 people. Analysis of research data using univariate and bivariate data analysis, this study uses chi square statistical test to find out. The results showed that there was no significant effect between sex on ARI disease in Nelayan Indah Village (P Value = 0.106 > = 0.05), there was no significant effect between age on ARI disease in Nelayan Indah Village (P Value = 817 > = 0.05), there is a significant effect between environmental health on ARI disease in Nelayan Indah Village (P Value = 0.000 < = 0.05), there is no significant effect between behavior/PKIP on ARI disease in Nelayan Indah Village (P Value = 0.968 > = 0.05), there is a significant effect between MCH (mother and child health) on ARI disease in Nelayan Indah Village (P Value = 0.000 < = 0.05).